New york, actually - Morgan, Sarah (From Manhattan with love, 2017)
Everything a romantic novel should be - an absolute delight.' - Veronica Henry meet Molly New York's most famous agony aunt, she considers herself an expert at relationships...as long as they're other people's. The only love of her life is her Dalmatian, Valentine